Airbnb, Grab, and Beyond: A Qualitative Study of Digital Intermediaries in Vietnam’s Urban Tourism - Nguyen, Tram (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
This study explores how digital platforms are reshaping the dynamics of tourism in urban Vietnam, with a focus on Airbnb, Grab, and other intermediaries. Drawing on semi-structured interviews with hosts, tourists, and service providers in Hanoi and Ho Chi Minh City, the research adopts a phenomenological approach to examine perceptions of trust, intimacy, and risk in digitally mediated encounters. The findings reveal that digital platforms extend beyond transactional functions by fostering new forms of social interaction, cultural exchange, and urban mobility. However, they also generate tensions around regulatory uncertainty, safety concerns, and the erosion of traditional hospitality practices. Hosts emphasized the dual role of platforms as enablers of economic opportunity and as mechanisms of surveillance and dependency, while tourists described a balance between convenience and a sense of detachment from authentic local life. By situating these experiences within debates on platformization and tourism, the study contributes to understanding how technology mediates host–guest relationships in emerging destinations. The results highlight the need for policies that safeguard cultural integrity and trust while supporting innovation in Vietnam’s rapidly expanding tourism economy.